Putative Cholinergic Interneurons in the Ventral and Dorsal Regions of the Striatum Have Distinct Roles in a Two Choice Alternative Association Task - Yarom, Orli; Cohen, Dana (Frontiers in Systems Neuroscience, 2011)
The striatum consists of GABAergic projection neurons and various types of interneurons. Despite their relative scarcity, these interneurons play a key role in information processing in the striatum. One such class of interneurons is the TANs, the cholinergic tonically active neurons. In the dorsal striatum, TANs are traditionally considered to be responsive to events of motivational significance. However, in recent years, studies have suggested that TANs are not exclusively related to reward and reward-predicting stimuli, but may contribute to other processes, including responses to aversive stimuli, detecting the spatial location of stimuli and generating movement. Currently there is little data concerning TAN activity in the ventral striatum (VS) of behaving animals. Here, we simultaneously recorded neurons in the ventral and the dorsolateral (DLS) regions of the striatum while animals performed a two choice alternative association task. Our data show that a large percentage of the putative TANs in both regions responded around movement initiation and execution. The majority of these neurons exhibited directional selectivity which was stronger in DLS relative to VS. In addition, the preferred directions in VS were mostly contralateral to the recording site whereas the observed preferred directions in DLS were equally distributed contralaterally and ipsilaterally to the recording site. The most interesting difference between DLS and VS was that DLS TANs maintained activity alterations throughout the movement whereas TANs in VS exhibited short-lasting phasic activity alterations that were maintained throughout the movement by different neurons. Our findings suggest that coding of movement by TANs in both regions overlaps to some degree, yet the differences in response patterns support the notion that the TANs in DLS participate in the motor loop whereas TANs in VS convey event-related information such as movement initiation, movement direction and end of movement.